Introduction: Homage to Walter Freeman III - O Nuallain, Sean (Cosmos and History: The Journal of Natural and Social Philosophy, 2016)
Introduction to the third special edition on the Foundations of Mind: Foundations of Mind: Hommage to Walter Freeman III